CuS Microspheres with Tunable Interlayer Space and Micropore as a High‐Rate and Long‐Life Anode for Sodium‐Ion Batteries. Issue 22 (28th May 2018) - Xiao, Yuanhua; Su, Dangcheng; Wang, Xuezhao; Wu, Shide; Zhou, Liming; Shi, Ying; Fang, Shaoming; Cheng, Hui‐Ming; Li, Feng
Abstract: Layered transition metal sulfides (LTMSs) have tremendous commercial potential in anode materials for sodium‐ion batteries (SIBs) in large‐scale energy storage application. However, it is a great challenge for most LTMS electrodes to have long cycling life and high‐rate capability due to their larger volume expansion and the formation of soluble polysulfide intermediates caused by the conversion reaction. Herein, layered CuS microspheres with tunable interlayer space and pore volumes are reported through a cost‐effective interaction method using a cationic surfactant of cetyltrimethyl ammonium bromide (CTAB). The CuS–CTAB microsphere as an anode for SIBs reveals a high reversible capacity of 684.6 mAh g −1 at 0.1 A g −1, and 312.5 mAh g −1 at 10 A g −1 after 1000 cycles with high capacity retention of 90.6%. The excellent electrochemical performance is attributed to the unique structure of this material, and a high pseudocapacitive contribution ensures its high‐rate performance. Moreover, in situ X‐ray diffraction is applied to investigate their sodium storage mechanism. It is found that the long chain CTAB in the CuS provides buffer space, traps polysulfides, and restrains the further growth of Cu particles during the conversion reaction process that ensure the long cycling stability and high reversibility of the electrode material. Abstract : Layered CuS–cetyltrimethyl ammonium bromide (CTAB) microspheres with tunable interlayer space and pore volume are synthesized through a cost‐effective interaction method with a cationic surfactant of CTAB. The CTAB layer in the interlayer space of CuS provides buffer space, traps polysulfides, and limits the size of generated Cu particles that ensure the long cycling stability.